The Influence of Influencer Credibility, Brand Image, and e-WOM on Consumer Purchase Intentions for Products Promoted through TikTok - Suci Mila Ramadhani; Heri Fitriyadi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of influencer credibility, brand image, and electronic word of mouth (e-WOM) on purchase intention for Wardah Facial Wash products on TikTok. Using a quantitative survey of 100 respondents, data were analyzed through validity and reliability tests and multiple linear regression via SPSS. Results show that while all three variables significantly affect purchase intention collectively, only brand image has a positive and significant individual effect. These findings highlight the dominant role of brand image over influencer credibility and e-WOM in shaping consumer purchase decisions in the TikTok marketing context.